The impact of entrepreneurship training and credit on the labour market outcomes of disadvantaged young people - Khan, Tahsina Naz; Bhattacharjee, Anindita; Das, Narayan; N. Hossain, Marzuk A.; Rahman, Atiya; Tabassum, Asma (Taylor and Francis, 2024)
This article was published in The Development in Practice [©2024 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/09614524.2024.2312387 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/09614524.2024.2312387